2021
DOI: 10.18632/aging.202688
|View full text |Cite
|
Sign up to set email alerts
|

Functional predication of differentially expressed circRNAs/lncRNAs in the prefrontal cortex of Nrf2-knockout mice

Abstract: In the central nervous system, nuclear factor erythroid-2-related factor 2 (Nrf2) protects neurons from oxidant injury, thereby ameliorating neurodegeneration. We explored the key circular RNAs (circRNAs) and long non-coding RNAs (lncRNAs) involved in Nrf2-induced neuroprotection. We used microarrays to examine the circRNAs (DEcircRNAs), lncRNAs (DElncRNAs) and mRNAs (DEmRNAs) differentially expressed between Nrf2 (+/+) and Nrf2 (-/-) mice and identified DEcircRNA/DElncRNA-miRNA-DEmRNA interaction networks. In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 60 publications
0
4
0
Order By: Relevance
“…Recent studies have shown that certain circ-RNAs can influence disease processes by regulating oxidative stress and modulating the Nrf2 pathway. Gao 29 et al found that the types and amounts of circ-RNAs in mouse prefrontal cortex were significantly different before and after Nrf2 knockdown, suggesting that circ-0000233, circ-0015035, and circ-0012936 may contribute to the effects of the Nrf2 pathway on cognitive function. In related reports on diabetes and its complications, circ-ITCH, circ-HIPK3, and circ-UBAP2 may regulate the Nrf2 pathway to influence oxidative damage.…”
Section: ■ Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent studies have shown that certain circ-RNAs can influence disease processes by regulating oxidative stress and modulating the Nrf2 pathway. Gao 29 et al found that the types and amounts of circ-RNAs in mouse prefrontal cortex were significantly different before and after Nrf2 knockdown, suggesting that circ-0000233, circ-0015035, and circ-0012936 may contribute to the effects of the Nrf2 pathway on cognitive function. In related reports on diabetes and its complications, circ-ITCH, circ-HIPK3, and circ-UBAP2 may regulate the Nrf2 pathway to influence oxidative damage.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Recent studies have shown that certain circ-RNAs can influence disease processes by regulating oxidative stress and modulating the Nrf2 pathway. Gao et al found that the types and amounts of circ-RNAs in mouse prefrontal cortex were significantly different before and after Nrf2 knockdown, suggesting that circ-0000233, circ-0015035, and circ-0012936 may contribute to the effects of the Nrf2 pathway on cognitive function. In related reports on diabetes and its complications, circ-ITCH, circ-HIPK3, and circ-UBAP2 may regulate the Nrf2 pathway to influence oxidative damage. ,, Among these, circ-ITCH would be used as a target for the remedy of diabetic kidney damage. , Circ-ITCH has also been mentioned several times in relation to liver damage. Our investigation indicated that TFDG upregulates circ-ITCH, which performs an essential function in regulating the Nrf2 pathway to protect against diabetic liver and kidney injury.…”
Section: Discussionmentioning
confidence: 99%
“…The length of circRNAs varies from 200-2000 nucleotides, with the majority having lengths of about 500 nucleotides, which are generally located in the cytoplasm. The direct ligation of the exonic downstream 5' donor site with the upstream 3' acceptor site results in a closed loop structure, which makes circRNAs resistant to degradation by exonuclease RNaseR and helps them maintain high stability and conserved sequence 43 . According to their origin, circRNAs may be composed of exons, introns and exon-intron structures (ElciRNA) 44 .…”
Section: Classification and Features Of Non-coding Rnasmentioning
confidence: 99%
“…Due to the generally mild impact of Cryptosporidium infection on host cell gene transcription compared to other pathogens [9][10][11][12], to obtain as many differentially expressed genes as possible, we chose fold changes > 2 combined with P ≤ 0.05 as the threshold to preliminarily screen differentially expressed circRNAs in the microarray analysis in our article [3]. The criterion of P <0.05 or P ≤ 0.05 was also used by recent studies [13][14][15][16]. From the subsequent verification of the experimental results, circRNAs of interest obtained using the threshold of P ≤ 0.05 are stable and accurate.…”
Section: To the Editormentioning
confidence: 99%